Description of upper intermoral dental arch size in thalassemia beta mayor aged 9-14 years old based on gender - Anggraini, Nana; Riyanti, Eriska; Chemiawan, Eka (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
Beta major thalassemia was characterized by severe hereditary hemolytic anemia and suffered from retardation in growth, and facial skeletal alteration also narrower arches. The purpose of this research was to obtain data on intermolar width in the 9-14 years old beta major thalassemia patients by gender at the Thalassemia Clinic of Pediatric Department Dr. Hasan Sadikin General Hospital Bandung. This research used the description method with survey technique. Sample collecting was by consecutive sampling resulting in a number of 57 samples and measurement in the model were allowed. Research result showed that the average of the intermolar width of beta major thalassemia patients age 9-10 (intermolar width 5,52 cm), 10-11 (5,10), 11-12 (5,28), 11-12 (5,46), 12-13 (5,52), and 13-14 (5,52). In 25 girls patient 9-10 (5,01), 10-11 (5,02), 11-12 (4,93), 12-13 (5,04), and 13-14 (5,13).The conclusion of this research was that intermolar width variated in every age range.